PRAANGGAPAN DALAM DRAMA DER KAUKASISCHE KREIDEKREIS KARYA BERTOLT BRECHT - FOA, BONAFANTURA (UNIVERSITAS NEGERI SURABAYA, 2016)
In interaction we use language. Language is a symbol vocal arbitrar that allows everyone in a given culture or others who study the culture system, communicate or interact. In use, the language is a pragmatic study. Pragmatics is the study of meaning in connection with language situations. In communicating often occurs language misunderstandings between the participants. Misunderstandings happened because of the participants have no common knowledge about the things that they discussed. Common knowledge which is owned by participants that background this speech called presupposition. This research, describes the presupposition that appeared in the drama der kaukasische Kreidekreis works of Bertolt Brecht, and the presuppositions influence on the continuity of communication. Presuppositions can be grouped into six of the presuppositions of Existential (existential presuppositions), presuppositions Faktif (factive presuppositions), presuppositions Lexical (lexical presuppositions), presuppositions Structural (structural presuppositions), presuppositions Non-faktif (non-factive presuppositions), and presuppositions Konterfaktual (counter -factual presuppositions). To identification  presuppositions also formulated in context. Context underlying the utterance is encapsulated in the acronym SPEAKING. The method used is descriptive qualitative approach. The used data is the transcript of drama der kaukasische Kreidekreis with the data is the dialog utterances that contains presuppositions indicators. Data obtained using literature study method. The results showed that all kinds of preconceptions appear. Another participant said the responses show continuity of communication is also described in the analysis results. With its presuppositions are equal, then communication is successful. Keywords: language, pragmatics, presuppositions.